2015
DOI: 10.1001/jamainternmed.2015.0914
|View full text |Cite
|
Sign up to set email alerts
|

Rates of Opioid Dispensing and Overdose After Introduction of Abuse-Deterrent Extended-Release Oxycodone and Withdrawal of Propoxyphene

Abstract: IMPORTANCEIn the second half of 2010, abuse-deterrent extended-release oxycodone hydrochloride (OxyContin; Purdue Pharma) was introduced and propoxyphene was withdrawn from the US market. The effect of these pharmaceutical market changes on opioid dispensing and overdose rates is unknown.OBJECTIVE To evaluate the association between 2 temporally proximate changes in the opioid market and opioid dispensing and overdose rates. DESIGN, SETTING, AND PARTICIPANTS Claims from a large national US health insurer were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
97
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(102 citation statements)
references
References 37 publications
(51 reference statements)
2
97
3
Order By: Relevance
“…Recently, 2 large studies from the US also showed significant reductions in the quantity of long-acting oxycodone dispensed following the introduction of a tamper-deterrent formulation. 18,19 In contrast to our findings, the authors reported no corresponding rise in the quantity of other long-acting opioids dispensed. These differences may be at least partially explained by changes in the public funding of OxyNeo in Canada, which may have led more patients to switch from oxycodone to an alternative opioid.…”
Section: Discussioncontrasting
confidence: 99%
“…Recently, 2 large studies from the US also showed significant reductions in the quantity of long-acting oxycodone dispensed following the introduction of a tamper-deterrent formulation. 18,19 In contrast to our findings, the authors reported no corresponding rise in the quantity of other long-acting opioids dispensed. These differences may be at least partially explained by changes in the public funding of OxyNeo in Canada, which may have led more patients to switch from oxycodone to an alternative opioid.…”
Section: Discussioncontrasting
confidence: 99%
“…[94][95][96][97][98][99] A growing body of evidence suggests that introduction of the abuse-deterrent formulation of oxycodone has been associated with decreased rates of abuse and diversion of this opioid analgesic in the USA. [101,[110][111][112][113][114][115][116][117][118][119]. Cost savings have also been reported to be associated with reductions in abuse following the introduction of the abuse-deterrent reformulation of oxycodone in the USA.…”
Section: Differences In Routes Of Abuse Between Populationsmentioning
confidence: 99%
“…However, these benefits have been accompanied by a significant increase in abuse of other opioids, most notably heroin, in some studies. [112,[116][117][118]122] Epidemiological data showing the potential impact of other abuse-deterrent opioid analgesic formulations on rates of prescription opioid abuse and diversion are not yet available.…”
Section: Differences In Routes Of Abuse Between Populationsmentioning
confidence: 99%
“…Prescription drug users frequently move onto heroin, an illegal and powerful opioid, because it is much less expensive and often easier to get; studies have shown almost half of young heroin users start with abusing prescription opioids [27,28]. A study reporting the effects of introducing an abuse-deterrent opioid showed that opioid dispensing dropped 19% and prescription opioid overdoses dropped 20%; however, heroin overdose rose 23% as a result [29]. Reducing the supply of opioids without addressing their demand can result in people turning to heroin and other harmful drugs [23,29].…”
Section: Health Systems and Policy Research Issn 2254-9137mentioning
confidence: 99%
“…A study reporting the effects of introducing an abuse-deterrent opioid showed that opioid dispensing dropped 19% and prescription opioid overdoses dropped 20%; however, heroin overdose rose 23% as a result [29]. Reducing the supply of opioids without addressing their demand can result in people turning to heroin and other harmful drugs [23,29].…”
Section: Health Systems and Policy Research Issn 2254-9137mentioning
confidence: 99%